Advancements in Global Positioning System Technology - Choudhary, Anuj Raj; Chaudhary, Neha; Sharma, Manoj Kumar (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2021)
The Global Positioning System which is also known as NAVSTAR GPS. It is a satellite dependent radio navigation system which is controlled by U.S government and operated by U.S space force. Major work of this Global Navigation Satellite System (GNSS) is to give the information about geolocation and time information to any operator on earth or in range of the line sight of four or more GPS satellites. The obstacles such as mountains and buildings block the radio signals from satellite. How to cite this article: Choudhary AR, Chaudhary N, Sharma MK. Advancements in Global Positioning System Technology. J Adv Res Geo Sci Rem Sens 2020; 7(3&4): 1-3.